Legitimasi Kitab Keagamaan terhadap Rencana Pemerintah dalam Pengembangan Wisata Kawasan Danau Toba - Nainggolan, Herrio T. (JURNAL DIAKONIA, 2022)
This paper examines the role and contribution of religious books, especially the Bible, to the government's plan for tourism development in the Lake Toba area, which is strongly influenced by anthropocentric interpretations. By using a qualitative research method with a literature study approach, this study reveals how the anthropocentrism perspective of religious texts strongly supports the government's plan to develop tourism in the Lake Toba area. This perspective explains that humans are the pinnacle of creation and the entire created world with all its wealth was created with the aim of human welfare and happiness, so that the created world is seen as an object of fulfilling human needs. Religious institutions, in this case the church leadership, also support the reason that the development of the Lake Toba area which is being launched by the government will improve the economy and people's welfare